2013
DOI: 10.1155/2013/673146
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Benign and Malignant Thyroid Nodules in Autoimmune Thyroid Diseases

Abstract: Objectives. Assess the prevalence of thyroid nodules and predictors of malignant origin in patients with autoimmune thyroid diseases. Patients and Methods. Retrospective study including 275 patients, 198 with Graves' disease and 77 with Hashimoto's thyroiditis. Clinical and demographical data, ultrasonographical nodule characteristics, total thyroid volume and histological characteristics were recorded. Results. Graves' disease: the prevalence of thyroid nodules and thyroid carcinoma were 27.78% and 5.05%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
0
16
0
6
Order By: Relevance
“…with AITD than in those without AITD and that they may be a 209 premalignant condition to PTC [20,21,22]. Our results, concerning 210 lymphoid cells, demonstrate unprecedently that these cells are 211 attacked by oxidative damage in PTC and AITD.…”
mentioning
confidence: 68%
“…with AITD than in those without AITD and that they may be a 209 premalignant condition to PTC [20,21,22]. Our results, concerning 210 lymphoid cells, demonstrate unprecedently that these cells are 211 attacked by oxidative damage in PTC and AITD.…”
mentioning
confidence: 68%
“…The malignancy rate in these nodules varies between 10% and 46% (10). This rate is approximately 5% in the general population (12). While the annual incidence of clinical thyroid cancer in the general euthyroid population has been reported to be 0.5-8/100.000, it is 175/100.000 in Graves disease (13).…”
Section: Resultsmentioning
confidence: 98%
“…(14) reported this rate to be 3.6% (n = 12). This shows that malignancy is not always related with nodule (12). If these patients were treated only with antithyroid and/ or radioactive iodine, they would not have received an appropriate treatment because of accompanying thyroid cancer (15).…”
Section: Resultsmentioning
confidence: 99%
“…Pinchot et al reported that thyroid carcinoma prevalence was higher in the elderly compared with others while Rosario and et al did not observe a significant difference between the age of the patients (6, 18). Nevertheless, some studies including ours, revealed that the prevalence of thyroid carcinoma is higher in the younger patients (19, 20). …”
Section: Discussionmentioning
confidence: 70%